In vitro testing of combined hydroxychloroquine and azithromycin on SARS-CoV-2 shows synergistic effect. (August 2020) - Andreani, Julien; Le Bideau, Marion; Duflot, Isabelle; Jardot, Priscilla; Rolland, Clara; Boxberger, Manon; Wurtz, Nathalie; Rolain, Jean-Marc; Colson, Philippe; La Scola, Bernard; Raoult, Didier
Abstract: Human coronaviruses SARS-CoV-2 appeared at the end of 2019 and led to a pandemic with high morbidity and mortality. As there are currently no effective drugs targeting this virus, drug repurposing represents a short-term strategy to treat millions of infected patients at low costs. Hydroxychloroquine showed an antiviral effect in vitro. In vivo it showed efficacy, especially when combined with azithromycin in a preliminary clinical trial. Here we demonstrate that the combination of hydroxychloroquine and azithromycin has a synergistic effect in vitro on SARS-CoV-2 at concentrations compatible with that obtained in human lung. Highlights: SARS-CoV 2 emergence and spreading need to found urgently therapeutics. Drug repurposing is the best strategy for quick therapeutic response. Azithromycin and hydroxychloroquine shows synergistic effect on replication . Concentrations of drugs are more compatible with in vivo concentrations.